2021
DOI: 10.1111/ajt.16385
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of kidney retransplantation in recipients with prior posttransplant lymphoproliferative disorders: An analysis of the 2000–2019 UNOS/OPTN database

Abstract: This study utilized the UNOS database to assess clinical outcomes after kidney retransplantation in patients with a history of posttransplant lymphoproliferative disease (PTLD). Among second kidney transplant patients from 2000 to 2019, 254 had history of PTLD in their first kidney transplant, whereas 28,113 did not. After a second kidney transplant, PTLD occurred in 2.8% and 0.8% of patients with and without history of PTLD, respectively (p = .001). Over a median follow‐up time of 4.5 years after a second kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Standard treatment includes induction with rituximab followed by either rituximab monotherapy in the event of complete remission, or a variation of R‐CHOP; however, in rare cases, the decreased immunosuppression alone results in complete remission [ 23 ] and it seems preferable to keep the immunosuppression as low as possible throughout follow‐up. More typically, further reduction in immunosuppression after remission of PTLD might not be beneficial, the rate of relapse being limited [ 24 ]; a re‐increase or modification seems possible, since some studies have shown very rare relapses after a new renal transplant [ 25 , 26 ]. However, currently, there is no recommendation on how to modify the immunosuppression, or on optimal timing between the response of PTLD and drug modification.…”
Section: Discussionmentioning
confidence: 99%
“…Standard treatment includes induction with rituximab followed by either rituximab monotherapy in the event of complete remission, or a variation of R‐CHOP; however, in rare cases, the decreased immunosuppression alone results in complete remission [ 23 ] and it seems preferable to keep the immunosuppression as low as possible throughout follow‐up. More typically, further reduction in immunosuppression after remission of PTLD might not be beneficial, the rate of relapse being limited [ 24 ]; a re‐increase or modification seems possible, since some studies have shown very rare relapses after a new renal transplant [ 25 , 26 ]. However, currently, there is no recommendation on how to modify the immunosuppression, or on optimal timing between the response of PTLD and drug modification.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,18 Nevertheless, kidney transplant patients, including recipients with kidney retransplant, are heterogeneous and there are many factors, including recipient, donor, and transplantrelated characteristics, that can result in varying outcomes. [2][3][4][5][6]19,20 Machine learning (ML), a subfield of artificial intelligence, has been applied to create clinical decision support tools and individualize patient care, including in kidney transplantation. [21][22][23][24][25][26] Studies have demonstrated that unsupervised ML consensus clustering can be utilized to discover novel data patterns and distinct subtypes, [27][28][29] and ultimately distinguish them into clinically meaningful clusters.…”
Section: Data From the United States Renal Data System And Canadianmentioning
confidence: 99%
“…As a result, some kidney transplant centers have lower kidney retransplant rates with highly selective criteria for retransplantation 9,17,18 . Nevertheless, kidney transplant patients, including recipients with kidney retransplant, are heterogeneous and there are many factors, including recipient, donor, and transplant‐related characteristics, that can result in varying outcomes 2–6,19,20 …”
Section: Introductionmentioning
confidence: 99%
“…Retransplantation was associated with a 68% lower adjusted risk of death compared with dialysis and this benefit was observed in all subgroups examined including diabetic patients, patients older than 60 years-old, and patients with PRA > 80%. [ 3 ] The survival benefit of retransplantation has been addressed in other specific subgroups including patients with previous posttransplant lymphoproliferative disorders [ 24 ], first graft loss due to BK nephropathy [ 25 ], third or fourth kidney retransplant [ 26 ], and older recipients [ 27 , 28 ] and found similar graft and patient survival rates. Even in patients older than 70 years-old, there was a slight survival advantage in retransplantation as opposed to remaining on dialysis after first graft failure [ 29 ].…”
Section: The Benefits Of Retransplantationmentioning
confidence: 99%